FORMULATION AND EVALUATION OF AN ORAL TIMED PULSATILE DRUG DELIVERY FOR ALLEVIATING PAIN IN RHEUMATOID ARTHRITIS - JYOTHIRMAYI, PASAM; BHARATHI, ARIGELA; REDDY, D. RAMA SEKHARA (International Journal of Applied Pharmaceutics, 2025)
Objective: The present study was aimed to formulate and evaluate an oral timed-release pulsatile drug delivery of AcecloFenac (AF) for rheumatoid arthritis pain by the Chronopharmaceutical approach with early morning breakthrough of AF as analgesic and anti-inflammatory agent for the treatment of rheumatoid arthritis. Methods: A solubility was enhanced by formulating it as a self-emulsified system with a suitable oil and surfactant mixture. The interaction between the drug and the excipient was examined using Fourier Transform Infra-Red (FTIR) spectroscopy. The prepared formulation consists of 2 different parts: The basic design consists of burst-release core tablets with solid self-emulsified AF by using different super disintegrants, and the press-coating of optimised tablets by using different compositions of Ethylcellulose (hydrophobic) and Hydroxy Propyl Methyl Cellulose (HPMC K100) (hydrophilic) polymers. Results: FTIR studies revealed no interaction between drug and excipients. From the solubility data, suitable oil and surfactants were selected. Pseudo-ternary plots help in finding of suitable surfactant mixtures for solid self-emulsified AF. Core tablets were evaluated for pre-compression characteristics, disintegration time, drug content, weight variation, hardness, friability, thickness, and % drug release. Among all solid self-emulsified formulations, S1C6 is successful, with 98.88% drug release in 20 min. The compression coat formulations were also evaluated for Hardness, weight variation, thickness, lag time, and in vitro drug release profile. Among them, F4 was optimised by its suitable lag time and drug release of 97.23% at the end of 6 h. Conclusion: The system released the drug after a predetermined lag time of 4 h and thus, the dosage form can be taken at bedtime so that the drug will be released when the symptoms are prominent. Nine formulations were prepared, of which F4 formulation showed the highest drug release of 97.23 % at the end of 6 h and showed compliance with the chronotherapeutic objective of rheumatoid arthritis.